(untitled) (Al-Qamar, 2020)
Crafting a commentary on the Holy Qur’an is not just an intellectual pursuit; it is a timeless art that requires a profound scholarly commitment. A commentator transcends the conventional role of a mere interpreter; they embody the qualities of a seasoned religious scholar, a meticulous lexicographer, and a dedicated custodian of Islamic history. Their intellectual breadth encompasses intricate subjects such as science and philosophy, and their scholarly pursuits extend to a diligent study of previous inspired texts, coupled with a comprehensive grasp of the vast reservoir of hadiths. Additionally, they remain acutely attuned to the dynamic conditions of their contemporary era. With a wealth of expertise garnered across these diverse fields, their interpretation of the Holy Quran’s verses is deeply rooted in a lifetime of accumulated knowledge. Each exegete, however, brings a unique style to the interpretation of the Qur’an, enhancing the richness of understanding the sacred verses. The individuality of their approach contributes to the nuanced tapestry of comprehending the Holy Quran, emphasizing its multifaceted nature and profound impact. The intrinsic value of comprehending the ayaat of the Holy Qur’an can’t be overstated. Since the inception of this nation in the name of Islam, it has been a magnet for great personalities who migrated here (Pakistan), and their enduring contributions continue to shape and benefit society. Among these luminaries was ‘Mufti Muhammad Shafi,’ a polymath who concurrently served as a mufti, jurist, and commentator. His Tafseer ’Tafseer Ma’arif al-Qur’an,’ spanning eight volumes, stands as a testament to comprehensive scholarship. Within this Tafseer, one encounters ‘signs’ and ’sayings of Salaf,’ woven into historical narratives and discussions on contemporary ijtihad issues. This comprehensive approach underscores the enduring significance and relevance of Maulana’s interpretation in the ever-evolving landscape of Islamic understanding.